Znanstveno-raziskovalni trendi na področju digitalne preobrazbe (University of Maribor Press, 2021)
Scientific Research Trends in the Field of Digital Transformation. The digital transformation of organizations is a key element for success in modern business. The readiness of management and employees in organizations, as well as expertise in digital transformation concepts and technologies, play an important role. This publication presents current digital transformation topics that can enable organizations and other stakeholders in the process of digital transformation to make a smoother transition to digital business. Several topics are presented that discuss breakthrough technologies in digital transformation. An overview of examples of multi-criteria expert decision systems is provided, followed by a presentation of the role of data in modern organizations, approaches to transforming business process models to blockchain technology, and guidance on securing the organization against pandemic cyber threats. In addition to the examples, a strategic information technology governance model is presented.